Humans have a basic physical and psychological need to move the body: Physical activity as a primary drive - Stults-Kolehmainen, Matthew A. (Frontiers in Psychology, 2023)
Physical activity, while less necessary for survival in modern times, is still essential for thriving in life, and low levels of movement are related to numerous physical and mental health problems. However, we poorly understand why people move on a day-to-day basis and how to promote greater energy expenditure. Recently, there has been a turn to understand automatic processes with close examination of older theories of behavior. This has co-occurred with new developments in the study of non-exercise activity thermogenesis (NEAT). In this narrative review, it is hypothesized that psycho-physiological drive is important to understand movement in general and NEAT, specifically. Drive, in short, is a motivation state, characterized by arousal and felt tension, energizing the organism to acquire a basic need. Movement is a biological necessity, like food, water, and sleep, but varying across the lifespan and having the greatest impact before adolescence. Movement meets various criteria for a primary drive: a) deprivation of it produces feelings of tension, such as an urge or craving, known as affectively-charged motivation states, and particularly the feelings of being antsy, restless, hyper or cooped up, b) provision of the need quickly reduces tension; one can be satiated, and may even over-consume, c) it can be provoked by qualities of the environment, d) it is under homeostatic control, e) there is an appetite (i.e., appetence) for movement but also aversion, and f) it has a developmental time course. Evidence for drive has mainly come from children and populations with hyperkinetic disorders, such as those with anorexia nervosa, restless legs syndrome, and akathisia. It is also stimulated in conditions of deprivation, such as bed rest, quarantine, flights, and physical restraint. It seems to be lacking in the hypokinetic disorders, such as depression and Parkinson’s. Thus, drive is associated with displeasure and negative reinforcement, subsuming it within the theory of hedonic drive, but it may fit better within new paradigms, such as the WANT model (Wants and Aversions for Neuromuscular Tasks). Recently developed measurement tools, such as the CRAVE scale, may permit the earnest investigation of movement drive, satiation, and motivation states in humans.